2017
DOI: 10.1021/acs.joc.7b00315
|View full text |Cite
|
Sign up to set email alerts
|

Diarylamino- and Diarylboryl-Substituted Donor–Acceptor Pyrene Derivatives: Influence of Substitution Pattern on Their Photophysical Properties

Abstract: Dianisylamino donor (D) and dimesitylboryl acceptor (A) substituents were introduced at the 1,6- and 2,7-positions of pyrene to demonstrate that the substitution patterns influence the photophysical properties. The different pictures in orbital interactions between the pyrene core and the D-A substituents led to the outcome that 1,6-substituted pyrene derivative 1 had stronger electron-donating and electron-accepting properties in conjunction with a small HOMO-LUMO gap, as compared to the 2,7-substituted deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 90 publications
2
45
0
Order By: Relevance
“…We note that Ito et al. have reported apparent Stokes shifts of the D‐π‐A compound H ranging from 3292 cm −1 in hexane ( λ max (em)=458 nm) to 8649 cm −1 in acetone ( λ max (em)=600 nm) . However, these very high values are the result of an incorrect excited state assignment.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…We note that Ito et al. have reported apparent Stokes shifts of the D‐π‐A compound H ranging from 3292 cm −1 in hexane ( λ max (em)=458 nm) to 8649 cm −1 in acetone ( λ max (em)=600 nm) . However, these very high values are the result of an incorrect excited state assignment.…”
Section: Resultsmentioning
confidence: 68%
“…Slightly and significantly shorter N−C bonds are observed in 11 (1.391(3) Å) and 6 (1.379(2) Å), respectively (Table ). In contrast, the N−C(pyrene) bond length of 1‐(dimesitylboryl)‐6‐(di‐4‐anisylamino)pyrene, a positional isomer of H (Scheme ) (1.442(4) Å), in which the functional groups are located at the 1,6‐positions, is significantly longer . The sum of the C‐N‐C angles involving the julolidine moiety is similar in compounds 4 , 8 , and 9 (350(1)° on average), slightly larger in 11 (355.7(6)°), and varying between about 344° and 350° in 14 (Table ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…[28] Moreover, previous studies demonstrated that strong p-donors/acceptors are able to switch the energetic ordering of its HOMO/HOMOÀ1 and LUMO/LUMO + 1, respec-tively, which results in greatly influenced photophysical and redox properties of these derivatives. [15,[29][30][31][32] Unsymmetrical substitution at these positions is straightforward via iridiumcatalyzed CÀH borylation, [33][34][35] and the introduction of julolidine-like donors at the 2,7-positions (I, Scheme 2) even resulted in an unusual green luminescence. [15,[29][30][31][32]36] The K-region (positions 4,5,9,10, Figure 1) has large HOMO/ LUMO as well as HOMOÀ1/LUMO + 1 contributions.…”
Section: Introductionmentioning
confidence: 99%
“…[15,[29][30][31][32] Unsymmetrical substitution at these positions is straightforward via iridiumcatalyzed CÀH borylation, [33][34][35] and the introduction of julolidine-like donors at the 2,7-positions (I, Scheme 2) even resulted in an unusual green luminescence. [15,[29][30][31][32]36] The K-region (positions 4,5,9,10, Figure 1) has large HOMO/ LUMO as well as HOMOÀ1/LUMO + 1 contributions. Ottonelli and co-workers showed [37] that the contribution to the HOMO/ LUMO increases in the order: 2,7 < 4,5,9,10 < 1,3,6,8, while contributions to the HOMOÀ1/LUMO + 1 increase in the order 4,5,9,10 < 1,3,6,8 < 2,7.…”
Section: Introductionmentioning
confidence: 99%